Methods Of Studying Louis De Broglie Wave And Corpuscular-Wave Dualism In The Course Of Physics In Academic Lyceums - et. al., Samatov Gulom Bazarbaevich, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The analysis of the textbooks of the physics course of academic lyceums shows that the content of the teaching materials in the department of quantum physics is sufficiently complex that it is briefly, vaguely described by the authors of the textbooks. Despite the fact that in recent years in the Russian Federation and Uzbekistan in this area have defended several dissertations, published textbooks and suggestions for improving teaching methods, the content of textbooks remains very shallow. Quantum physics is the basis of modern physics, a great contribution to the development of physics and technology. adds. It is well known that microcosm phenomena are subject to statistical laws, macrocosm, or physical phenomena studied on the basis of classical physics are mainly subject to dynamic laws, but systems consisting of many particles studied on the basis of classical physics, such as gaseous and liquid properties, are also subject to statistical laws. The phenomena of the microworld are studied on the basis of quantum physics, in contrast to the phenomena of the macroworld, the state of each particle in the microworld has a statistical character. Thus, the phenomena studied on the basis of quantum physics are based on probabilistic-statistical laws [3.4,5]. In the physics course of lyceums the basic ideas of teaching methods of the department of quantum physics with the correct formulation of the content of teaching materials and the application of probabilistic-statistical laws are presented. Currently, in the physics textbooks of secondary schools and academic lyceums in the Republic and the Russian Federation, the department of quantum physics is mainly limited to a detailed study of the photoelectric effect and Compton effect, a brief description of the corpuscular-wave dualism. [10,11,12] For this reason, students' perceptions of quantum physics remain shallow. The authors teach the experimental foundations of quantum physics, ie the laws of radiation of an absolutely black body, the concept of quantum, photoeffect, Compton effect, De Broglie waves and its probabilistic-statistical interpretation, wave function, are invited to add topics. [9,20] Pedagogical experiments were conducted on the proposed content of quantum physics in the areas of in-depth study of physics in academic lyceums, resulting in a sharp increase in students' interest in learning the basics of modern physics [7,9,14]. The presented article is devoted to the study of De Broglie waves and their possible statistical interpretation topics.